Centrosomal AKAP350 and CIP4 act in concert to define the polarized localization of the centrosome and Golgi in migratory cells - Tonucci, Facundo Mauro (2015)
The acquisition of a migratory phenotype is central in processes as diverse as embryo differentiation and tumor metastasis. An early event in this phenomenon is the generation of a nucleus-centrosome-Golgi back-to-front axis. AKAP350 (also known as AKAP9) is a Golgi and centrosome scaffold protein that is involved in microtubule nucleation. AKAP350 interacts with CIP4 (also known as TRIP10), a cdc42 effector that regulates actin dynamics. The present study aimed to characterize the participation of centrosomal AKAP350 in the acquisition of migratory polarity, and the involvement of CIP4 in the pathway. The decrease in total or in centrosomal AKAP350 led to decreased formation of the nucleus-centrosome-Golgi axis and defective cell migration. CIP4 localized at the centrosome, which was enhanced in migratory cells, but inhibited in cells with decreased centrosomal AKAP350. A decrease in the CIP4 expression or inhibition of the CIP4-AKAP350 interaction also led to defective cell polarization. Centrosome positioning, but not nuclear movement, was affected by loss of CIP4 or AKAP350 function. Our results support a model in which AKAP350 recruits CIP4 to the centrosome, providing a centrosomal scaffold to integrate microtubule and actin dynamics, thus enabling centrosome polarization and ensuring cell migration directionality.